Multicenter randomized trial of endoscopic papillary large balloon dilation without sphincterotomy versus endoscopic sphincterotomy for removal of bile duct stones: MARVELOUS trial - Kogure, Hirofumi; Kawahata, Shuhei; Mukai, Tsuyoshi; Doi, Shinpei; Iwashita, Takuji; Ban, Tesshin; Ito, Yukiko; Kawakami, Hiroshi; Hayashi, Tsuyoshi; Sasahira, Naoki; Kubota, Kensuke; Togawa, Osamu; Kato, Hironari; Okabe, Yoshinobu; Matsubara, Saburo; Yagioka, Hiroshi; Saito, Tomotaka; Nakai, Yousuke; Isayama, Hiroyuki (Endoscopy, 2020)
Background Endoscopic papillary large balloon dilation (EPLBD) has been increasingly used for the management of large common bile duct (CBD) stones. Although EPLBD is often preceded by endoscopic sphincterotomy (EST), EPLBD alone without EST has been increasingly reported as an alternative to EST for large CBD stones.Methods This multicenter randomized trial was conducted at 19 Japanese institutions to compare the efficacy and safety of EPLBD alone versus EST for the removal of large (≥ 10 mm) CBD stones. The primary end point was complete stone removal in a single session. The secondary end points included: overall complete stone removal, lithotripsy use, procedure time, adverse events, and cost.Results 171 patients with large CBD stones were included in the analysis. The rate of single-session complete stone removal was significantly higher in the EPLBD-alone group than in the EST group (90.7 % vs. 78.8 %; P = 0.04). Lithotripsy use was significantly less frequent in the EPLBD group than in the EST group (30.2 % vs. 48.2 %; P = 0.02). The rates of early adverse events were comparable between the two groups: rates of overall adverse events were 9.3 % vs. 9.4 % and of pancreatitis were 4.7 % vs. 5.9 % in the EPLBD and EST groups, respectively. The procedure costs were $1442 vs. $1661 in the EPLBD and EST groups, respectively (P = 0.12).Conclusion EPLBD without EST for the endoscopic treatment of large CBD stones achieved a significantly higher rate of complete stone removal in a single session compared with EST, without increasing adverse events.